Trends in research related to fetal therapy from 2012 to 2022: a bibliometric analysis - Jia, Yang; Liang, Xiaoling; Liu, Lini; Ma, Huixi; Xu, Chenhao; Zeng, Jingyuan; Xu, Rong; Ye, Lu; Xie, Linjun (Frontiers in Pediatrics, 2024)
The development of prenatal diagnosis technology allows prompt detection of severe fetal diseases. To address adverse factors that threaten fetal survival, fetal therapy came into existence, which aims to preserve the function after birth to a higher degree and improve the quality of life.Objective: To conduct a comprehensive bibliometric analysis of studies on fetal therapy in the past decade and explore the research trends and hotspots in this field.We conducted a systematic search on the Web of Science Core Collection to retrieve studies related to fetal therapy published from 2012 to 2022. VOSviewer and CiteSpace were used to analyze the key features of studies, including annual output, countries/regions, institutions, authors, references, research hotspots, and frontiers.Results: A total of 9,715 articles were included after eliminating duplicates. The annual distribution of the number of articles showed that the number of articles published in fetal therapy had increased in the past decade. Countries and institutions showed that fetal therapy is more mature in the United States. Author analysis showed the core investigators in the field. Keyword analysis showed the clustering and emergence frequency, which helped summarize the research results and frontier This is a provisional file, not the final typeset article hotspots in this field. The cocited references were sorted out to determine the literature with a high ranking of fetal therapy in recent years, and the research trend in recent years was analyzed.This study reveals that countries, institutions, and researchers should promote wider cooperation and establish multicenter research cooperation in fetal therapy research. Moreover, fetal therapy has been gradually explored from traditional surgical treatment to gene therapy and stem cell therapy. In recent years, fetoscopic laser surgery, guideline, and magnetic resonance imaging have become the research hotspots in the field.